What Do International Students Need? The Role of Family and Community Supports for Adjustment, Engagement, and Organizational Citizenship Behavior - Chai, Dae Seok; Van, Huyen Thi Minh; Wang, Chih-Wei; Lee, Jin; Wang, Jia (Journal of International Students, 2020)
This study aimed to investigate the relationships between perceived family support and community support and the organizational citizenship behavior of international students in U.S. higher education institutions. It also examined the mediating effects of cross-cultural adjustment and engagement on the relationships. Data were collected from 1,436 international students in one university located in the southwestern United States. Building on previous studies that have used a top-down managerial approach, this study used a noninstitutional/person-based approach to validate two guiding theories (spillover theory and job demands–resources model) and related former empirical studies. The results help stakeholders visualize a holistic picture of the international student experience. Such knowledge enables higher education institutions to make data-driven decisions about how to strategically prioritize resources to assist international students.